O casamento entre o tempo e a eternidade: uma análise à luz da comunhão plena de vida, da proteção da confiança e do direito intertemporal - Tereza Cristina Monteiro Mafra (2013)
The present work has the intention of analyzing the plain communion of life and the protection of the confidence in the intertemporal rule of wedding. The plain communion of life is an angular stone of wedding and affects all its aspects. Besides the protection of confidence should lead the wedding too, it’s assistematic and punctual in jurisprudence. The objective, after analyzing the historical development of wedding, is to check if and how the plain communion of life and the confidence protection may serve as instrument to systematize the interpretation and application of wedding norms with intertemporal rule, facing the lack of doctrine material around the subject. The theoretical framework is composed by the wedding comprehension as an institution, adopted by Paul Roubier and followed by several Brazilian writers, the idea that the life communion is wedding as state and must exist in both plans, personal and patrimonial, and the negotiating view of wedding, suffering the incidence of characteristics of confidence, maintained by Menezes Cordeiro and Carneiro da Frada.